2009
DOI: 10.1136/ard.2009.107623
|View full text |Cite
|
Sign up to set email alerts
|

Severe fibrotic changes and altered expression of angiogenic factors in maternal scleroderma: placental findings

Abstract: In SSc placentas, severe fibrosis and abnormal vascular remodelling were detected. This may result in reduced blood flow leading to deep sufferance of maternal placenta and possible premature delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…We then investigated the expression of IL33 and ST2 in a wide array of visceral organs which are affected by the fibrotic process in SSc including lung, kidney, heart, gastrointestinal tract and placenta 1 35 27. Lung, kidney, heart, and oesophageal autopsy samples were obtained from two subjects with early severe dcSSc with rapidly progressive disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then investigated the expression of IL33 and ST2 in a wide array of visceral organs which are affected by the fibrotic process in SSc including lung, kidney, heart, gastrointestinal tract and placenta 1 35 27. Lung, kidney, heart, and oesophageal autopsy samples were obtained from two subjects with early severe dcSSc with rapidly progressive disease.…”
Section: Resultsmentioning
confidence: 99%
“…We carefully selected healthy specimens that appeared to have no inflammatory/neoplastic infiltration according to histopathological examination. Placenta biopsies were obtained after delivery from three women with SSc (two lcSSc, one dcSSc) and four healthy uncomplicated pregnancies matched to SSc cases for gestational age, as described previously 27. All specimens were fixed in formalin and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…Only one previous study has addressed this issue (7), and the results of that study showed a prevalence of IUGR in patients with SSc (5.3%) that was similar to that observed in our study. The placental vasculopathy that can develop in SSc might be responsible for this outcome (19).…”
Section: Discussionmentioning
confidence: 99%
“…Lidia Ibba-Manneschi et al [8] reported that pregnant women with scleroderma are at increased risk of pathological change with severe and diffuse perivascular and stromal fibrosis of decidua and chorionic villi, and extensive deposition of fibrinoid material around decidual vessels and in intervillous spaces. These ischemic changes may induce the cystic changes at the surface of the placenta.…”
Section: Discussionmentioning
confidence: 98%